Flouting Maxim in Netizen's Utterance on The Comment Page Popo Barbie Tik Tok Account - Helmita Helmita; Rini Afrilesa J (Fakultas Sastra Universitas Ekasakti, 2021)
The cooperative principle proposed by Grice stated “make your contribution such as is required, at the stage at which it occurs, by the accepted purpose or direction of the talk exchange in which you are engaged”, but in the real life communication, this principle was often being flouted which was known as flouting maxim. This research aimed to describe the flouting maxim phenomenon in one of Indonesian Social Media,Tik Tok Application. From the analysis of the collected data, the writers found that some conversation of netizens in the comment page in Popo Barbie Tik Tok account contained flouting maxim, whether it is flouting maxim of quantity, quality, relevance, and also manner. When the flouting maxim happened, it contained certain implicature, in which the speaker intended to deliver certain implicit message, such as assuring the hearer, and giving mocking”